Agroecological aspects of winter wheat productivity techniques - T. V. Kononova; A. K. Shkhapatsev; S. V. Zhilenko; Y. N. Ashinov (Новые технологии, 2018)
The influence of Turion fungicide and Elant Premium herbicide on the growth, development and productivity of winter wheat on leached chernozems in the Krasnodar Territory has been determined. The use of fungicides for dressing seeds of winter wheat before sowing has increased its yield. As a result of the studies, a positive effect of the joint use of fungicide, herbicide and complex mineral fertilizers on the formation of productivity of winter wheat agrocenosis has been determined.